Automatic generation of battle maps from replay data. (July 2018) - Wallner, Guenter
With the advent of online gaming, access to in-game data has become increasingly important for players as it provides great opportunities for them to reflect and improve upon their gameplay or to compare their performance with others. Some of the currently most popular games focus on strategy and tactics, requiring players to skillfully position and maneuver units in order to achieve victory in battle. However, current visualizations for retrospective analysis of battles and that are targeted toward players are mainly limited to heatmaps and hence are not well suited for conveying the flow of battle. By contrast, military planners and historians alike have long used maps to provide a concise visual overview of troop movements. In this article, we are proposing an algorithm for automatically creating such battle maps from tracked in-game data. Several parameters allow to adjust the level-of-detail in the resulting maps. To demonstrate the practicality of our approach for post hoc analysis, we apply it to actual gameplay data obtained from a massively multiplayer online game and collected preliminary feedback among players of the game through an online survey.